Dinophysis spp. asociadas a detección de toxinas diarreicas (DSTs) en moluscos y a intoxicación diarreica en humanos (Provincia de Buenos Aires, Argentina) - Sar, Eugenia A. (2010)
During January and February 2010 lipophilic shellfish toxins were detected in two bivalve species from Villa Gesell and Mar Azul (Argentina) by the mouse bioassay method and potentially toxigenic species of Dinophysis were consistently found with densities of the order of 103 to 104 cell l-1 in the phytoplankton. Additionally, three cases of human gastrointestinal illness associated with the consumption of cooked wedge clams (Donax hanleyanus) collected in Villa Gesell were reported. The consumed shellfish was positive for lipophilic toxins by the mouse bioassay and the human diseases were consistent with diarrhoetic shellfish poisoning (DSP). This is the first record of detection of an outbreak of diarrhoetic shellfish poisoning associated to the presence of Dinophysis species in Argentina. The species identified were Dinophysis acuminata and D. caudata, previously associated to the detection of diarrhoetic toxins in clams (Mesodesma mactroides), wedge clams and mussels (Mytilus edulis) from the coastal waters of Uruguay.